Types, psalms, and prophecies being a series of Old Testament studies - Baron, David, 1855-1926 (London, UK Hodder and Stoughton, 1907)
Includes bibliographical references.
Donated by the late T.C. Denton
Keywords: Bible. O.T. -- criticism, interpretation, etc; Bible. O.T. -- typology